Molecular rotation in p-H₂ and o-D₂ in phase I under pressure - Freiman, Yu.A.; Tretyak, S.M.; Goncharov, A.F.; Mao, H.; Hemley, R.J. (Физика низких температур, 2011)
The orientational order parameter, rotational ground-state energy, and lattice distortion parameter (the deviation of the c/a ratio from the ideal hcp value 1.633) in hcp lattice of phase I of p-H₂ and o-D₂ are calculated using a semi-empirical approach. It is shown that the lattice distortion in these J-even species is small compared with that found in n-H₂, and n-D₂. The difference presumably is caused by the J-odd species.